A framework for building a learning organisation in the 21st century. (25th February 2005) - Sharma, Sushil K.; Gupta, Jatinder N.D.; Wickramasinghe, Nilmini
The concept of the learning organisation that strives continually to develop its people and processes is now accepted by many as a competitive necessity in today's business environment (Drucker, 1999; Davenport and Prusak, 1998). Organisations are increasingly being challenged to leverage learning, as it has been widely articulated that knowledge creation and continuous learning at the individual, team, and organisational levels may be the only source of sustainable competitive advantage. Organisations of the future will not be able to expand into new markets and win market share unless they have a coherent framework (technologies, people, processes and methodologies) to systematically and effectively use their past knowledge to gain a competitive advantage. Many organisations claim that they have initiated measures to convert their organisations from a traditional model to the learning model. However, we believe critical knowledge gaps exist in understanding of how to exploit technologies to create a suitable framework for a learning organisation. This paper attempts to address this apparent void. Our framework sets up guidelines for the building of learning organisations.